2009
DOI: 10.1111/j.1439-0434.2008.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Diversity among Botrytis cinerea Isolates in Iran

Abstract: Forty-four Botrytis cinerea isolates from different hosts and geographical regions were studied for colony morphology, mycelial growth rate at different temperatures, pathogenicity and molecular diversity. Botrytis cinerea isolates had temperature optima of 20-25°C and isolates showed variation in growth rate at different temperatures. Two morphological types were identified among tested isolates: mycelial and sclerotial. The pathogenicity of isolates was tested on grapevine leaves, and it was revealed that ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Regarding the phenotypic characterization, the three B. cinerea strains, selected as representative strains of all isolates according to the UPGMA dendrogram, differed in mycelial growth rates measured in laboratory (MEA) and natural (grape juice) media. Variations on growth rates among several B. cinerea isolates were previously described (Martinez et al ., ; Mirzaei et al ., ). Of particular importance was the pathogenicity assay carried out on berries in order to select potential strains to use for postharvest infection to obtain artificially grape botrytization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the phenotypic characterization, the three B. cinerea strains, selected as representative strains of all isolates according to the UPGMA dendrogram, differed in mycelial growth rates measured in laboratory (MEA) and natural (grape juice) media. Variations on growth rates among several B. cinerea isolates were previously described (Martinez et al ., ; Mirzaei et al ., ). Of particular importance was the pathogenicity assay carried out on berries in order to select potential strains to use for postharvest infection to obtain artificially grape botrytization.…”
Section: Discussionmentioning
confidence: 99%
“…Typing B. cinerea isolates, by RAPD‐PCR, confirmed that gray rot populations are characterized by a high level of heterogeneity, as reported by previous investigations (Thompson & Latorre, ; Alfonso et al ., ; Mirzaei et al ., ). These strains were not related to geographic origin as evidenced also by cluster A of the UPGMA dendrogram that included indigenous isolates and the reference strain DSM 877.…”
Section: Discussionmentioning
confidence: 99%
“…It causes extensive pre-and post-harvest damages and infects over 200 plant species worldwide. B. cinerea is not host specific and shows virulence variation towards different host plants (Mirzaei et al, 2009). This fungus is a complex pathogen due to its high flexibility in adapting to various host plants and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The fungus has been reported to infect more than 200 crop species worldwide, such as grapes, stone fruit, berries, and vegetables, and the losses in yield before and after harvest are extensive (Williamson et al, 2007). B. cinerea is not host-specific, and its virulence varies in different plant hosts (Derckel et al, 1999; Mirzaei et al, 2009). Because it has a broad host spectrum and causes significant economic losses, B. cinerea has been considered as the second most important fungal pathogen worldwide (Dean et al, 2012).…”
mentioning
confidence: 99%